Improving healthcare services for living kidney donors: an experience-based approach in the Netherlands - Sipma, Wim S.; van Londen, Marco; Visser, Annemieke; de Jong, Margriet F. C.; Ahaus, Kees C. T. B. (Frontiers in Public Health, 2025)
Living kidney donors voluntarily donate one of their kidneys to someone suffering from end-stage kidney disease. Transplantation is a life-saving opportunity for these patients and generally provides an increase in quality of life. A major goal of research and practice related to living kidney donation concerns the safety of the donor. In comparison, only limited research has been carried out on donor experiences of the donor journey in the full cycle of care. To gain further insight into this, we have performed an experience-based co-design (EBCD) study in a major transplant center in the Netherlands. EBCD is a research approach where professionals and patients share experiences with the purpose of improving the healthcare journey. We identified 11 areas for potential improvement: from intake, throughout surgery and hospitalization, to homecare and aftercare. Donors indicated the importance of person-specific information during the admission process, accurate communication with health professionals and attention to recovery after surgery. Nevertheless, no one regretted their donation, and the overall experience was positive. An important finding for professionals is that donors feel like ‘normal’ patients and want to be taken care of even though they are healthy. Just like other patients, they can be anxious before surgery and some may have concerns about recovery. Although this is a single-center study, the results should be relevant for all transplant centers that are interested in improving donor experiences. We concluded that the EBCD approach, when embedded in a local context, is a valuable tool for bringing patients’ experiences to healthcare improvement.